Factors associated with vitamin D and gestational diabetes mellitus among pregnant women in selected maternal and child health clinics in Seremban, Negeri Sembilan, Malaysia - Palaniveloo, Lalitha (2021)
The prevalence of Vitamin D deficiency (VDD) is high among pregnant women in Malaysia despite abundance of sunlight all year round. VDD had been associated with many adverse effects in pregnancy and one of them is gestational diabetes mellitus (GDM). Thus, this study aimed to investigate the association between Vitamin D status in first trimester with GDM among pregnant women in selected maternal and child health clinics in Seremban, Negeri Sembilan. This study was a part of the ‘Seremban Cohort Study (SECOST): A prospective study of determinants and pregnancy outcomes of maternal glycemia in Malaysia’. In this study, 170 pregnant women were recruited using purposive sampling method from Senawang and Ampangan Maternal and Child Health Clinics in Seremban, Negeri Sembilan between 2014 - 2015 and followed-up until 2016. A set of pre-tested Malay language interviewer-administered questionnaire was used to obtain information on demographic, socio-economic, dietary intake and physical activity. Obstetrical data were obtained from the antenatal cards of the women. Height and weight of the women were measured in the clinics at the study enrollment (<10 weeks), during Visit 1 (10-14 weeks of gestation) and Visit 2 (24-30 weeks of gestation). Blood samples were obtained during Visit 1 to quantify serum 25-Hydroxy Vitamin D [25(OH)D] and during Visit 2 for a standard 75g Oral Glucose Tolerance Test (OGTT). VDD is defined as serum 25(OH)D <50nmol/L. GDM is diagnosed if fasting plasma glucose ≥ 5.6 nmol/L or 2-hours post prandial plasma glucose ≥ 7.8 nmol/L. All data were analysed using SPSS version 22 and significant level was set at p<0.05. Logistic regression was performed to determine the association between serum Vitamin D status in first trimester and GDM. The prevalence of VDD in first trimester and GDM in the present study was 93% and 14.1% respectively. Pregnant women who had pre-pregnancy BMI of overweight/ obese were 6 times more likely to have mild VDD compared to pregnant women with normal BMI while pregnant women with a family history of Type 2 Diabetes Mellitus (T2DM) were 3 times more likely to have GDM compared to pregnant women who do not have any family history of T2DM. In this study, pregnant women with GDM had a significantly higher mean Vitamin D level compared to non-GDM pregnant women in bivariate analysis. However, serum Vitamin D status was not significantly associated with GDM in the multivariate analysis. In the study, pregnant women with GDM had a higher mean pre-pregnancy BMI and age compared to non-GDM pregnant women. These two factors could have contributed to the onset of GDM regardless of Vitamin D level. A more comprehensive study with a bigger sample size is suggested to obtain concrete evidence on the association between VDD in pregnancy and GDM as only 24 women were diagnosed with GDM in this study.